Activation of Homolytic SiZn and SiHg Bond Cleavage, Mediated by a Pt0 Complex, via Novel PtZn and PtHg Compounds. Issue 40 (18th August 2015) - Kratish, Yosi; Molev, Gregory; Kostenko, Arseni; Sheberla, Dennis; Tumanskii, Boris; Botoshansky, Mark; Shimada, Shigeru; Bravo‐Zhivotovskii, Dmitry; Apeloig, Yitzhak
Abstract: The thermally stable [( t BuMe2 Si)2 M] (M=Zn, Hg) generate R3 Si . radicals in the presence of [(dmpe)Pt(PEt3 )2 ] at 60–80 °C. The reaction proceeds via hexacoordinate Pt complexes, (M=Zn (2 a and 2 b ), M=Hg (3 a and 3 b )) which were isolated and characterized. Mild warming or photolysis of 2 or 3 lead to homolytic dissociation of the PtMSiR3 bond generating silyl radicals and novel unstable pentacoordinate platinum paramagnetic complexes (M=Zn (5 ), Hg (6 )) whose structures were determined by EPR spectroscopy and DFT calculations. Abstract : SiM City : The thermally stable [( t BuMe2 Si)2 M] (M=Zn, Hg) generate R3 Si . radicals in the presence of [(dmpe)Pt(PEt3 )2 ]. The enhancing effect of the Pt complex on the homolytic cleavage of the SiM bonds in [( t BuMe2 Si)2 M] is mediated by formation of octahedral hexacoordinate PtM trinuclear complexes.